Climate change resilience in the Canadian Arctic: The need for collaboration in the face of a changing landscape ... - MacDonald, Seghan; Birchall, Jeff S. (University of Alberta Library, 2019)
Human-induced changes to global climate have become increasingly difficult to ignore in recent years. As the frequency and severity of extreme weather events increases, the impacts on both natural and human systems are becoming difficult to manage with the current policies. In Canada, one of the most vulnerable regions to climate change is the Arctic, where temperatures are rising at a rate two to three times that of the global average. Warmer seasonal temperatures have led to melting permafrost and increased variability in sea ice conditions, which has contributed to a rise in coastal erosion. The ongoing resilience of Arctic communities will depend heavily on their ability to implement successful long-term adaptation policies. The development and implementation of any action on climate change adaptation should involve collaboration with local stakeholders in order to reflect the views and experience of those living in the Arctic. ...